Chinese Americans' perceptions of race, education, and affirmative action - Lin, Shasha (Palgrave Macmillan, 2025)
Chinese Americans have emerged as increasingly prominent and influential actors in the decades-long debates over affirmative action in college admissions, which was struck down by the US Supreme Court in June 2023. Despite being portrayed as the Asian origin group least supportive of affirmative action, little is understood about how the broader Chinese American community makes meanings around this complex and contested policy. Drawing on ethnographic observations in California and diverse viewpoints from students, parents, organizational leaders, activists, college admissions consultants, and educators within the Chinese American community, this book probes the nuanced and divergent ways Chinese Americans make sense of race, education, and affirmative action. It finds a community grappling with the potent Asian admissions myths, questions of fairness in college admissions, and their positioning within racial discourses and politics. This book is a timely contribution to the much-needed dialogue on race, ethnicity, and higher education in the post-affirmative action era. It is also a must-read for university policymakers who aim to (re)establish public trust amidst declining confidence in higher education and heightened judicial and public scrutiny of their admissions policies and practices. Shasha Lin is Postdoctoral Research Associate at the Collaborative Research Centre "Heimat(en)" at Universität Heidelberg, Germany. Her research is at the crossroads of American studies, sociology, and political science. Her main research interests include race and ethnicity, Chinese diaspora, and Asia and Asia America
Keywords: Hochschulschrift